Pengaruh Literasi Keuangan, Tujuan Investasi, dan Influencer terhadap Keputusan Investasi Generasi Z - Christy, Vincent; Nasution, Siti Aisyah; Ginting, Wenny Anggresia (Fakultas Ekonomi Prodi Akuntansi, 2026)
The purpose of this study is to examine how Generation Z is influenced by financial literacy, investment objectives, and influencers in the Indonesian stock market. A total of 40 Generation Z individuals who are actively involved in the Indonesian stock market were given questionnaires as part of the quantitative research methodology. Using SPSS software version 25, tests of normality, multicollinearity, heteroscedasticity, autocorrelation, t-tests, F-tests, and the coefficient of determination (R²) were conducted to analyze the data. The research findings indicate that, both partially and simultaneously, the three independent variables—financial literacy, investment objectives, and influencer influence—have a positive and significant effect on investment decisions. These three variables account for 72.5% of the variation in investment decisions, while the remaining 27.5% is influenced by other factors outside the scope of this study, as indicated by the adjusted coefficient of determination (Adjusted R²) of 0.725.